Comparative study of the copolymerization kinetics of mono and divinylbenzyl p-tert-butylcalix[4]arene derivatives and styrene - Costa, Alexandra I. (2020)
A study of the copolymerization kinetics of 25,27-bis(4-vinyl-benzyloxy)-26,28-dihydroxy-p-tert-butylcalix[4]arene (1) and 25,26,27-tripropoxy-28-(4-vinyl-benzyloxy)-p-tert-butylcalix[4]arene (2) with styrene (St) was undertaken. The radical copolymerizations were carried outin THF in thepresence ofbenzoyl peroxideat 758C for a certain period. Six molar feed ratios, ranging from 1:1 to 1:20 (1 or 2 to St), were used to calculate the reactivity parameters. The copolymer composition was determined by FT-IR spectroscopy using a Beer’s law plot obtained from the corresponding homopolymers. The reactivity ratio calculations were performed with the linearization methods of Fineman-Ross (F-R) and Kelen-Tu ¨do ¨s (K-T), assuming the validity of the so-called terminal model. In the copolymerization of the monoene 2, similar reactivity ratios were found for the comonomers (ca. 1.2; K-T). On the other hand, the reactivity ratios calculated for the copolymerization of 1 with St yielded rSt 5 0.67 and rcalix 5 3.0 (K-T method). The higher reactivity of monomer 1 as compared to styrene is discussed in connection with our previously postulated cyclocopolymerization route.